Optimized production of CD2V extracellular domain of African swine fever virus on adherent culture baculovirus- Sf9 insect cell system - Nguyen, Thu Giang; Ho, Thi Thuong; Chu, Hoang Ha; Pham, Bich Ngoc (Vietnam Journal of Biotechnology, 2025)
The baculovirus expression vector system (BEVS) is one of the strongest tools for producing recombinant proteins such as pharmaceuticals and vaccines. In this study, the multivalent CD2v extracellular domain (CD2v ED) of the African swine fever virus (ASFV) was expressed in Sf9 insect cells using BEVs. Bacmid carrying the gene encoding CD2v ED-Foldon-His was transfected into Sf9 insect cells using the lipid transfer complex Cellfectin II and Opti-MEM I Reduced Serum Medium. The transfection process was observed under microscopy and protein expression would be assessed by western blot. The results indicated the transparent differences in infected cells, including the swelling of cells, the increase of nuclei, granular and vesicular appearance, cessation of cell growth, detachment from the flask bottom, and cell lysis in comparison with normal cells that are round, small, and regular size. The western blot results illustrated the expression of CD2v ED-Foldon-His in trimeric and oligomeric forms with bands of 100 kDa and more than 250 kDa, respectively. Most importantly, the expression of CD2v ED-Foldon-His in adherent culture insect cells was optimized with two main factors, namely multiplicity of infection (MOI) and infection time. The results demonstrated the highest yield of CD2v ED-Foldon-His protein was 4.4 mg/L at a MOI of 5 pfu/cell and 5 days post-infection, which was confirmed by captured pictures throughout the infection time. This is the first study on the expression of the oligomeric CD2v extracellular domain on a baculovirus-insect cell system, aiming to produce subunit vaccines against ASFV. Besides, the study also presented a practical procedure for enhancing the expression of recombinant proteins in this system.